A scheduling strategy to inter-satellite links assignment in GNSS. Issue 1 (1st January 2021) - Yan, Jungang; Xing, Lining; Wang, Pei; Sun, Leyuan; Chen, Yingwu
Highlights: Build a multi-objective optimization model for inter-satellite links assignment. A multi-objective scheduling strategy based on NSGA-II is proposed. Design the optimal operator combination for NSGA-II. The proposed strategy has improved the ranging and communication performance. Abstract: By introducing inter-satellite link (ISL), the dependence of the global navigation satellite system (GNSS) on ground infrastructure can be reduced and its performance enhanced via inter-satellite ranging and communication. Owing to platform restrictions, there are usually fewer onboard Ka-band ISL antennas than the number of visible satellites, which poses a problem when optimizing the inter-satellite links assignment of the GNSS. In this study, to optimize inter-satellite ranging and communication, a multi-objective optimization model is built and a scheduling strategy is proposed for the inter-satellite links assignment scheduling problem. The position dilution of precision (PDOP) of links and the transmission time-delay of telemetry data are set as the ranging performance and communication metrics, respectively. We regard the links assignment in each slot as a general graph-matching problem, and apply the Blossom algorithm to obtain the maximum matching. We then generate and optimize the satellite sequences for whole slots using non-dominated sorting genetic algorithm II (NSGA-II). The simulation scenes include 10, 080 epochs of GNSS constellation, and the simulation results show that the performance of the proposed strategy is better than that of other methods published recently, and can provide various solutions to meet the different preferences of system managers.